Management and Control of Occupational Risks in the Manufacture of Fuel and Oil Filter Caps - Ron-Valenzuela, Pablo (2021)
In the process of manufacturing oil and fuel filter covers, mechanical risks have been identified such as: entrapment and crushing of hands with risk level I (not acceptable) and projection of fragments and particles with risk level II (Not acceptable or acceptable with specific control); For this, corrective measures were established at the source of risk by means of a spring system in each of the molds so that the filter cover after being pressed is expelled uniformly without the need for the operator to insert his hands in the danger zone. In the accident transmission medium, an adjustable safety guard and a mechanical guide element were implemented which allow the entry and exit of the covers. Finally, workers were provided with work gloves selected under international standards